Calcium Alginate Foams Prepared by a Microfluidic T-Junction System: Stability and Food Applications - Ahmad, B; Stride, E; Edirisinghe, M (2012)
Highly porous alginate foams were prepared via a novel route in which highly viscous alginate solutions were bubbled using a microfluidic T-junction device. The relationship between bubble size and bubbling conditions such as air pressure and solution flow rate was studied, and the ability of the T-junction setup to generate monodisperse microbubbles (mean diameter, ~154 μm) and produce porous foams was systematically investigated. The foams were characterised by optical and scanning electron microscopy. Foams of varying lengths (12-45 mm) were successfully prepared using this technique, with an average density of ~235 kg/m 3. The pore diameter within the foams was determined by microscopy to be in the range of 600 nm-200 μm with a mean diameter of ~31 μm. It was concluded that porosity in the foam (>90%) can be varied depending on the initial bubble size. Thus, a possible production method of stable highly porous solid foams for exploitation in food and bioprocess technologies is presented by which products can be made to different sizes. © 2011 Springer Science+Business Media, LLC.